Empowering Learning: The Mediating Role of Teachers in Enhancing Students' Intrinsic Motivation - Netty Merdiaty; Sulistiasih Sulistiasih (STAI Hubbulwathan Duri, 2024)
This study explores the role of teachers as mediators in fostering students' intrinsic motivation—a key driver of independent and sustained learning. Intrinsic motivation encourages engagement in educational activities for personal satisfaction and growth, which is critical for academic and character development. A qualitative descriptive approach was employed to examine teacher-student interactions at a junior high school in Bandung City. Data were collected through observations, in-depth interviews, and documentation involving both teachers and students. The findings revealed that teachers significantly influence intrinsic motivation by acting as mediators and motivators. Strategies such as aligning teaching methods with students' interests, providing emotional and academic support, and creating an engaging learning environment enhance active participation. Furthermore, appropriately challenging tasks, constructive feedback, and meaningful praise bolster students' self-confidence and perseverance. These teacher-mediated practices not only improve academic outcomes but also foster students' self-worth and enthusiasm for learning. The results underscore the importance of a student-centered approach, which values individual needs and preferences, in cultivating a supportive and motivating educational environment. Teachers, by employing adaptive and engaging strategies, play a pivotal role in enhancing intrinsic motivation, thereby shaping a more effective and enjoyable learning experience. Future research should investigate the long-term impacts of these methods across diverse educational settings to refine their application and extend their benefits.